THE ANALYSIS OF THE FIRM SIZE INFLUENCE TO THE RATE OF STOCK RETURN (CASE IN THE COMPANIES LISTED IN LQ 45) - Hanum, Ayu Noviani (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2006)
The economic crisis has been destroying Indonesian economic since several years ago. The government had taken many efforts to recover the crisis. One of the effective medium to accelerate the economic recovery is by increase the activity in capital market. Capital market is an improvement board that is really interesting to the investors. It is one of the medium for the investors to invest their fund. The functions of the capital market are as an alternative fund collector beside the bank institutions. The capital market also make possible the investors to have many investment alternatives adjusted with the preference of investor risk. By invested their fund to the capital market, the investors expect that they will get capital gain from their investment. The companies that issued their stock in capital market called as issuer. By issuing their stock, they expect that they will get any earning in the form of high liquidity, publicity, prestige and capital gain that will be given to the investor. The capital gain that will be received by the investors can be derived from the dividend yield and stock return. Stock return is the excess in selling price from its buying price. Generally it declares as the percentage from the buying price. More higher the selling price from the buying price, the stock return will increase. So, the indicator of the return fluctuation is the selling price and buying price of the holding stock. According to Sharpe (1997:98), the main determination in the demand and supply of the stock is the investor’s estimation to the stock return and dividend that will be distributed. Because of the reasons above, the perception of the investor to the companies performance will determine the price of the stock.. The companies that predicted would have a good performance was expected by the investors in giving a big amount of dividend payment and stock return.